Monitoring and Control of Large Systems with MonALISA. - LEGRAND, IOSIF; VOICU, RAMIRO; CIRST OIU, CATALIN; GRIGORAS, COST IN; BETEV, LATCHEZAR; COSTAN, ALEXANDRU (Communications of the ACM, 2009)
The article focuses on the development of MonALISA, or Monitoring Agents using a Large Integrated Services Architecture, which is an application for controlling and monitoring large-scale distributed data-processing systems. The MonALISA framework, which was created by the California Institute of Technology's high energy physics group and has four layers of network look-up services, is explained. Research strategy focused on synergetics for computing, network infrastructure, applications, and storage facilities. The use of MonaALISA by the European Organization for Nuclear Research is mentioned.